Vehicle yaw stability control using active rear steering: Development and experimental validation. (June 2017) - Zhang, Baozhen; Khajepour, Amir; Goodarzi, Avesta
In this paper, a novel pulse active steering system for improving vehicle yaw stability is developed. In the proposed method, pulses are sent to the steerable rear wheels whenever the error between the expected and actual yaw rate is outside a predetermined range. The proposed method and its performance are verified experimentally by full vehicle testing. For this purpose, a simplified vehicle model and a rear suspension model are developed. Vehicle stability is investigated and the steering pulse parameters on the vehicle's stability are studied. A control system is designed and numerical simulations are performed. Moreover, the active rear steering system is implemented on a Lexus for performing road experiments. Results from simulations and experiments indicate that considerable improvement in the yaw stability performance can be achieved by the proposed system. The proposed method is more cost effective and simpler for vehicle stability control.